PENGARUH GAYA KEPEMIMIPINAN OTORITER DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN BAGIAN COMPONENT FACTORY DRY BATTERY DIVISION PADA PT SUKINEM MAKMUR ABADI - Rezeki, Fitri (Jurnal Ilmiah Multidisiplin, 2024)
Entering the era of globalization, the business competition that occurs between companies is getting tougher. The higher the competition and the less economic opportunities and the success rate of a company. So that companies must be able to build and increase the productivity of their employees, the existence of quality human resources in the company plays a role. The purpose of this study is to determine the influence of authoritarian leadership style and work environment on the performance of employees of the Component Factory Dry Battrey Division at PT Sukinem Makmur Abadi. The research method used is quantitative research in the form of surveys. The research sample was 100 employees of the Component Factory Dry Battrey Division at PT Sukinem Makmur Abadi. The data collection method uses questionnaires. The data analysis technique uses multiple linear regression tests, partial hypothesis tests using t tests, and simultaneous hypothesis tests using F tests>. (2) There is a significant influence of the work environment on employee performance obtained thitung = 6,840 > ttabel = 1.66, so that H2 is accepted. (3) There is a significant influence of authoritarian leadership style and work environment simultaneously on employee performance, with a regression line equation of Yˆ = 5.155 + 0.373.X1 + 0.449.X2 with the value Fhitung = 35.882 > Ftabel = 4.89, so that H3 is accepted. The conclusion of this study is that the variables of authoritarian leadership style and work environment have a significant effect on employee performance.